Penguatan Pendidikan Karakter melalui Kurikulum Muatan Lokal di SMP Muhammadiyah 2 Taman - Muhammad Arif Syaifuddin; Eni Fariyatul Fahyuni (PALAPA, 2019)
Moral setbacks that occur in adolescent level students experience a significant increase, not infrequently these events occur in the world of education in Indonesia. Strengthening character education is one way to reduce the effects of moral loss on students. So that the character values must be built in accordance with religious teachings and which have been determined by the government such as religiosity, mutual cooperation, independence, national and integrity. These values can be included in school programs through the integration of intraculicular, kokulikuler and extracurricular integration. In this study focuses on strengthening the existing character education in SMP Muhammadiyah 2 Park by including character habituation through local content learning, extracurricular activities and habituation activities. So it can be ensured that all student activities are based on strengthening character education. This study uses descriptive-qualitative research which results of the research are a translation of the sources obtained in the form of written and oral data and environmental observations.